Clinical Phytoscience International Journal of Phytomedicine and Phytotherapy - Bachert, Claus
Clinical Phytoscience is an international, peer-reviewed, interdisciplinary, and open access journal publishing high quality research articles on clinical evidence and use of medicinal plants in the development of efficient and well tolerated phytotherapy. Clinical Phytoscience focuses on phytotherapy, looking at proof of concept, efficacy and safety, to be established “at eye level” compared to pharmacotherapy. The emphasis lies on application oriented topics (efficacy and safety of phytotherapy in a specific indication, including its need and acceptance by the patient). The scientific results published in the journal should contribute to the recovery and maintenance of human health by phytotherapy. Clinical Phytoscience will publish high-quality evidence-based clinical studies and relevant pharmacological studies. Key areas of interest are: Upper and lower airways, ENT and pneumology Gynecology Urology Nephrology Pediatrics Intestinal tract Hepatology Diabetes/metabolic Syndrome Immunology and microbiology Hygiene Analytics The journal publishes original contributions, review articles (upon invitation; applications may be sent to the Editor in Chief) and short communications (letters). Articles are published after a rigorous and independent peer-review by an international board of experts. The journal is directed at medical doctors in clinic and practice and pharmacologists. Clinical Phytoscience does not accept purely descriptive pre-clinical work without translational aspects for publication.